2018
DOI: 10.1021/acs.orglett.8b02972
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular Desulfitative Coupling: Nickel-Catalyzed Transformation of Diaryl Sulfones into Biaryls via Extrusion of SO2

Abstract: As a new transformation of organosulfur compounds, intramolecular desulfitative coupling of diaryl sulfones to the corresponding biaryls has been developed with the aid of nickel− NHC catalysts. This catalytic elimination of SO 2 was also applicable to alkenyl aryl sulfone to furnish the corresponding alkenyl arene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 63 publications
1
22
0
Order By: Relevance
“…Based on the previous literature reports, [13][14]19] a plausible catalytic cycle in Scheme 3 was proposed. The reaction of Ni(acac) 2 and HL1 .…”
Section: Communicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the previous literature reports, [13][14]19] a plausible catalytic cycle in Scheme 3 was proposed. The reaction of Ni(acac) 2 and HL1 .…”
Section: Communicationsmentioning
confidence: 99%
“…The arylation proceeded in 28% yield when KOH was used [15][16][17]. Ni(OAc) 2 and NiBr 2 were also applied to the coupling, but both of them were almost inactive ( Table 1, entries [18][19]. We found that increasing the loading of Ni(acac) 2 to 7.5 mol% from 5.0 mol% can further improve the reaction yield to 89% (Table 1, entry 20).…”
mentioning
confidence: 99%
“…This is common even for other related metal-free biaryl syntheses exploiting the Truce-Smiles rearrangement in aryl sulfonamides and aryl phenylsulfonates [44][45][46] or the [3,3]-sigmatropic rearrangement of sulfonium salts arising from the reaction of aryl sulfoxides and phenols [47]. To overcome this problem, the use of a metal catalyst (mainly Ni) was mandatory as reported for the real extrusion of CO in diaryl ketones [48,49] or of SO 2 in diaryl sulfones (Scheme 1c) [50]. Nevertheless, a recent publication demonstrated that a metal-free photoextrusion was feasible when starting from benzene sulfonamides I (Scheme 1d, path a) [51].…”
Section: Metal-free Synthesis Of Biarenes Via Photoextrusion In Di(trmentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ = 3.73 (s, 3 H, ArOCH 3 ), 3.87 (s, 3 H, ArOCH 3 ), 6.72 (br, 1 H, NH), 6.84 (d,J = 8.0 Hz,1 H,ArH),2 H,ArH),3 H,ArH), 7.57-7.65 (m, 4 H, ArH), 7.83 (d,J = 8.0 Hz,2 H,ArH).…”
Section: Syn Thesismentioning
confidence: 99%
“…1 H NMR (400 MHz, CDCl 3 ): δ = 3.73 (s, 3 H, ArOCH 3 ), 6.84 (d, J = 8.0 Hz, 1 H, ArH), 7.09 (br, 1 H, NH), 7.32 (d, J = 8.0 Hz, 2 H, ArH), 7.42-7.67 (m, 10 H, ArH), 7.78 (d,J = 8.0 Hz,4 H,ArH). 2, 113.5, 124.9, 127.4, 127.8, 127.9, 128.4, 128.6, 128.7, 129.1, 129.2, 131.3, 133.3, 136.9, 139.1, 140.6, 146.1, 155.2. HRMS (ESI-TOF): m/z [M + Na] + calcd for C 25 H 21 NO 5 S 2 Na: 502.0753; found: 502.0755.…”
Section: N-(4-methoxy-3-(phenylsulfonyl)phenyl)-[11′-biphenyl]-4-sulmentioning
confidence: 99%